UPAYA PEMBARUAN HUKUM NASIONAL DI BIDANG KONTRAK JUAL-BELI BARANG INTERNASIONAL - Taufiqurrahman Taufiqurrahman (Yuridika, 2010)
United Nations Convention on Contracts for the International Sale of Goods 1980 (CISG) is one of monumental product to respond the need practically of the business actors in international trade traffic. CISG is not only containing substantive rules, but also containing procedures in determining the law applicable to disputes faced. The analytical result indicates that legal concept that can be developed for future governing choice of law in international business transaction is by establishment of the consent to be bound by the CISG. In that establishment, it is recommended that Indonesia puts aside the application of Article 1 (1) (b) of the CISG valued does not reflect the appreciation of state sovereignty.